Molecular cloning and in silico studies of physiologically significant trehalase from drosophila melanogaster - Shukla, Ekta; Thorat, Leena; Bhavnani, Varsha; Bendre, Ameya D.; Pal, J. K.; Nath, B. B.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Trehalase, a physiologically important glycosidase is known for its crucial role in insect glycometabolism and stress recovery. The present study describes the molecular cloning of a gene fragment, encoding the catalytically active trehalase from Drosophila melanogaster (DmTre) and its heterologous expression in Escherichia coli. The 1275 bp gene was overexpressed in two different vectors viz., pET28a and pCOLD TF and investigated for variable soluble expression, purification and activity of the recombinant enzyme with optimum pH and temperature of enzyme as 6 and 55 degrees C, respectively. The sequence was characterized in silico by subjecting it to homology search, multiple sequence alignment and phylogenetic tree construction revealing its identity to other trehalases which belong to glycoside hydrolase family 37. The deduced amino acid sequence and modeled 3D structure of DmTre possessed all features of trehalase superfamily, including signature motifs and catalytic domain. The active site pocket of recombinant DmTre was compared with the crystal structure of E. coli trehalase identifying Glu424 and Asp226 as the putative catalytic residues. Additionally, enzyme-substrate docking suggests possible involvement of other residues in the catalysis along with Asp226. The present study holds significance in understanding the structural aspects of Drosophila trehalase in spite of unavailabilty of eukaryotic trehalase crystal structure. (C) 2016 Elsevier B.V. All rights reserved.